FEATURES OF FUNCTIONING OF FINANCIAL MARKETS UNDER CONDITIONS OF GLOBAL INSTABILITY - ANANIEV, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the peculiarities of the functioning of financial markets in conditions of global instability, as well as the influence of factors contributing to this: geopolitical tensions, economic fluctuations and systemic risks. The elements of the financial market are defined: the totality of financial assets; the system of financial institutions (state management and control bodies and market financial infrastructure); technologies for concluding agreements for the purchase and sale of financial assets; the totality of operations on the purchase and sale of financial assets. The total assets of Ukrainian commercial banks were analyzed from 2008 to 2021. It was noted that the structure of the assets of Ukrainian banks is quite diverse and includes such components as cash, bank deposits, loan portfolios, securities, real estate and other assets. Therefore, when analyzing bank assets, it is important to pay attention to their structure and quality, which can significantly affect the financial results of banks and the overall stability of the country's financial system.In order to study the peculiarities of the functioning of financial markets in conditions of global instability, an analysis of the main factors that can affect the stability and risks of financial markets was carried out. The author of the article explored the role of global factors such as economic instability, political and geopolitical risks, trade conflicts, and national and international regulatory policies.The main conclusions of the article show that financial markets are very sensitive to changes in the external environment and economic events, so risk management in financial markets is an extremely important task. The article noted the importance of an effective regulatory policy that can ensure stability and protection of financial markets from threats.The importance of understanding the interrelationships between the financial and real sectors of the economy, as well as the impact of information technologies on financial markets, is emphasized. Research into these aspects can help improve risk management in financial markets and ensure their stability in a global context.In general, the study contributes to the understanding of the complex and important issue of the functioning of financial markets in global conditions of instability, makes it possible to understand the main factors that affect the stability of financial markets, and emphasizes the need for an effective regulatory policy to ensure their stability and protection from various threats. The results of the study can be useful for economic researchers, risk management professionals, as well as for government and regulatory bodies in the field of finance.
Keywords: financial markets; global instability; finances; factor; securities